KARAKTERISTIK BRIKET ARANG DARI CAMPURAN TEMPURUNG KELAPA DAN SERBUK GERGAJI KAYU PALAPI (Heritiera Sp) - Hapid, Abdul; Muthmainnah, Muthmainnah; Ahmad, Ahmad (ForestSains, 2018)
The current high population rate leads to inevitable, greater demand for energy. In fact, most urban communities depend on oil and gas as the energy source for daily usage while the communities in rural and  remote  areas  preferably  use  woods  as  fuel.  The  search  for  alternative  source  to  reduce  thedependency on the availability of fuelwood has been done by utilizing agricultural waste, industrial waste and  domestic  waste,  including  coconut  shells  and  sawdust.  These  wastes  can  be  processed  into briquettes as potential solid fuel. The present study aims to investigate the quality of briquettes made from a mixture of coconut shells and palapi sawdust. It was done in May to July 2016 at the Mechanical Engineering Labolatory, Tadulako University. A completely randomized design (CRD) was employed, withthree treatments: A (100% coconut shell charcoal), B (85% sawdust + 15% coconut shell charcoal) and C (85% coconut shell charcoal + 15% sawdust). The parameters included density, moisture, volatile matter, ash, and fixed carbon. The results showed the average moisture, ash, fixed carbon, volatile mater, and density of charcoal briquettes were: 4.62–4.99%, 4.51–5.55%, 29.63–53.17%, 36.94–59.88% and 0.48–0.7g/cm3, respectively. It indicates that the mixture of coconut shell and sawdust has a very significanteffect on ash content, volatile matter, fixed carbon and density, but insignificant effect on water content.